Are desensitizing toothpastes equally biocompatible and effective against microorganisms? - Camargo, Samira Esteves Afonso [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Saraiva, Fernanda de Oliveira [UNESP]; de Oliveira, Jonatas Rafael [UNESP]; de Oliveira, Luciane Dias [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP] (FapUNIFESP (SciELO), 2017)
The aims of this study were evaluate cytotoxicity, genotoxicity, antimicrobial activity of desensitizing toothpastes compared to a common one and the surface roughness of tooth enamel submitted to brushing with these toothpastes. Samples of three desensitizing toothpastes (Colgate Sensitive, Sensodyne and Oral B Sensitive) and common toothpaste (Colgate) were placed in contact with gingival human fibroblasts. Cytotoxicity and genotoxocity were measured by MTT assay and micronucleus test. Antimicrobial activity of the toothpastes extracts against C. albicans, S. mutans and S. aureus were assessed. For surface roughness evaluation, bovine teeth were submitted to 10.000 brushing cycles. The results were analyzed statically using Mann-Whitney U, ANOVA and Z tests (p<0.05). All toothpastes caused cytotoxic effect to the cells (p<0.05), except Colgate Sensitive. The toothpastes did not increase the number of micronuclei compared to the untreated control group. Colgate eliminated all the evaluated microorganisms at lower concentrations compared to Colgate Sensitive and Oral B Sensitive, which were not able to eliminate S. aureus. Sensodyne did not reach the minimum microbicidal concentration. The surface roughness of tooth enamel increased after brushing with Colgate Sensitive and Oral B Sensitive, however the comparison between groups showed no difference on the enamel surface roughness presented by desensitizing toothpastes when compared with the common one (p>0.05). Based on these results, we can conclude that although none toothpaste has induced genotoxicity, Colgate Sensitive was also not cytotoxic. Colgate was the most effective against the microorganisms, and there were no differences on the enamel surface roughness between the groups.
Keywords: Antimicrobial; Biocompatibility; Desensitizing; Roughness; Toothpastes